Factors Affecting Internal Audit Effectiveness with Application of Computer-Assisted Audit Techniques as a Moderating Variable - Sianturi, Gomgom Parluhutan; Anwar, Choirul; Amrizal (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
Driven by the internal audit ineffectiveness and fraud cases occurrence in various ministries/agencies, this quantitative study examines contribution of competence, autonomy, managerial support, communication and use of Computer-Assisted Audit Techniques (CAATs) to internal audit performance in the Ministry of Finance Inspectorate General, using CAATs as a balancing variable. Data was obtained through purposive sampling survey with a questionnaire and analyzed with SmartPLS 3.0 software. The findings are that knowledge, autonomy, management assistance, communication and the use of CAAT all have positive and significant impacts on internal audit performance. In addition, CAAT use moderates the association between competence and internal audit effectiveness, but has no effect on the associations between independence, management support, or communication and internal audit effectiveness. This paper will fill a research need by analysing CAAT implementation as a moderating factor and how it influences internal audit effectiveness. It also calls for improved internal auditor competence, autonomy, management support and communication and best practice implementation of CAAT based on the organisational requirements.